The Advertisement Call of Proceratophrys pombali (Amphibia: Anura: Odontophrynidae) with Comments on its Distribution and Natural History - Malagoli, Leo R. [UNESP]; Mangia, Sarah; Haddad, Celio F. B. [UNESP] (Soc Brasileira Herpetologia, 2016)
We describe the advertisement call of Proceratophrys pombali and provide data on its distribution and natural history in Nucleo Curucutu, Parque Estadual da Serra do Mar, Itanhaem, Sao Paulo, Brazil, and Mongagua, Sao Paulo, Brazil. Additionally, we specify the precise location of the type locality and detail the environments where the species occurs. The advertisement call is composed of a single, multipulsed note, and its dominant frequency is the highest recorded for the P. appendiculata complex. The species has explosive reproduction and its distribution restricted to the central region of the Serra do Mar of the state of Sao Paulo.
Keywords: Atlantic Forest; Bioacoustics; Brazil; Sao Paulo State; Serra do Mar